An Innovative Methodology to Assess the Vulnerability of Earthquake-prone Heritage Buildings to Climate-induced Floods in New Zealand - Aigwi, Itohan Esther; Ge, Yijun; Nwadike, Amarachukwu Nnadozie (Emerald, 2025)
Purpose: As climate change continues to escalate, the urgent challenge of protecting heritage structures vulnerable to earthquakes in flood-prone areas cannot be ignored. Conducting thorough vulnerability assessments is essential to tackle this pressing issue, aligning with the United Nations’ Sustainable Development Goals 11 and 13 and New Zealand’s National Climate Change Adaptation Plan. Design/methodology/approach: This study introduces an index-based approach to evaluate the flood vulnerability of earthquake-prone heritage buildings in Auckland, New Zealand, taking into account the evolving climate patterns. Data collection involved document analysis, on-site observations and mapping of ten earthquake-prone heritage buildings in Auckland. Findings: The results reveal significant variations in 11 identified flood vulnerability indicators across the selected buildings, categorised into “Exposure”, “Susceptibility” and “Resilience”. The type of use, surface condition, number of storeys and finishing material of the façades were identified as the most influential indicators affecting the flood vulnerability of the selected buildings. Originality/value: The study’s findings offer significant insights for stakeholders involved in the preservation of earthquake-prone heritage buildings in New Zealand, particularly in the context of increasing flooding risks from climate change. By providing a robust decision-making framework, the study enables local communities, heritage organisations and government bodies to collaborate more effectively in safeguarding cultural assets. The introduction of a quantitative intervention priority index is a valuable tool for assessing flood vulnerability, enabling stakeholders to prioritise resources and actions based on specific indicators. Ultimately, these insights will help protect New Zealand’s rich heritage and support its flood resilience efforts.
Keywords: 33 Built Environment and Design; 13 Climate Action; 11 Sustainable Cities and Communities; 12 Built Environment and Design; New Zealand; Heritage buildings; Earthquake-prone; Flood vulnerability; Index-based approach; Climate change